2020
DOI: 10.1101/2020.11.24.20237750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nurses’ burnout and associated risk factors during the COVID-19 pandemic: a systematic review and meta-analysis

Abstract: BackgroundDuring the COVID-19 pandemic, physical and mental health of the nurses is greatly challenged since they work under unprecedented pressure and they are more vulnerable to the harmful effects of the disease.AimTo examine the impact of the COVID-19 pandemic on nurses’ burnout and to identify associated risk factors.MethodsWe followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines for this systematic review and meta-analysis. PubMed, Scopus, ProQuest and pre-print servi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
86
3
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 85 publications
(210 reference statements)
17
86
3
5
Order By: Relevance
“…A systematic review and meta-analysis, published in March 2021 [ 44 ], identified 16 studies on nurses working with COVID-19 patients. The estimated prevalence of EE was 34.1% (95% CI = 22.5–46.6%), of DP 12.6% (95% CI = 6.9–19.7%), and of LPA 15.2% (95% CI = 1.4–39.8%).…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review and meta-analysis, published in March 2021 [ 44 ], identified 16 studies on nurses working with COVID-19 patients. The estimated prevalence of EE was 34.1% (95% CI = 22.5–46.6%), of DP 12.6% (95% CI = 6.9–19.7%), and of LPA 15.2% (95% CI = 1.4–39.8%).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, HCP who provided care to suspected or confirmed cases displayed higher levels of burnout symptoms as compared with their colleagues who did not involve in direct care delivery. 10 , 12 The relationships between burnout symptoms and professions were also documented in different studies, yet the directions remained inconclusive. 45 , 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that about 22%–51% of the surveyed HCPs display symptoms of burnout. 7 , 8 , 9 , 10 , 11 , 12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The COVID-19 pandemic affects physical and mental health of HCWs in several ways causing burnout, anxiety, insomnia, depression, sleep disturbances, skin reactions, dyspnoea, etc. [4][5][6][7] Moreover, HCWs have to work long hours under enormous pressure and very challenging circumstances.…”
Section: 3%mentioning
confidence: 99%